On Google Translate: Students’ and Lecturers’ Perception of the English Translation of Indonesian Scholarly Articles - Menik Winiharti; Syihabuddin Syihabuddin; Dadang Sudana (Bina Nusantara University, 2021)
The research investigated the translation results of Google Translate based on the users’ perceptions. It was aimed at describing the users’ frequency in using Google Translate web, finding the users’ perceptions on the acceptability and the readability of Google Translation in translating scholarly articles from Indonesian into English, as well as finding whether students and lecturers have the same perceptions regarding these two criteria. The data were collected from scholarly articles written in Indonesian then translated into English using Google Translate web. Then a survey regarding this translation was distributed to users; they were students and lecturers of Computer Science/Information Technology/Information System. The analysis was conducted with regard to the acceptability and the readability of the translations using a rating scale of translation assessment. The findings suggest that more than half of the participants often use Google Translate Web, which means that the academics are part of the users of Google Translate. However, students and lecturers have a rather different perception of the results of Google Translate. Students consider Google Translate quite acceptable and readable, while lecturers view Google Translate as rather acceptable and moderately readable. In addition, the findings indicate that, to some extent, Google Translate still translates the Indonesian text into English literally.